Study the Impact of Quality Control on Production Processes - Zahra, Ameen Ali (Al-Nahrain Journal for Engineering Sciences, 2020)
The research aims to improve the quality of the product through improving the quality of production processes by relying on the principle of quality control, the aim of this research is to identify the reality of quality control in the industrial public sector companies in Syria, and explaining the advantages of using the principle of quality control producing information and data that contribute to improve the quality of production, where the research was based on theoretical side to provide an explanation on the quality and its objectives and the principle of quality control and production processes, but on the practical side, the workers were surveyed at the General Company for Wool and Carpets in Hama.To achieve the objective of the research and to prove or deny the impact of quality control on the quality of production processes was based on the descriptive analytical method and using the appropriate statistical methods, where statistical analysis was carried out using SPSS 19 program.The statistical results have shown that there is a strong correlation between the quality control and improving the quality of production processes.The researcher recommended the need to form an administrative structure or forming a team work to improve the quality or using the consultants and researchers in order to supervise on the principle of quality control.